METHADONE AND MORPHINE FOR THE TREATMENT OF NEONATAL ABSTINENCE SYNDROME: A COMPARISON OF SAFETY AND EFFICACY - MAQSOOD, I; QAZI, GA; HAMAYUN, Z (Biological and Clinical Sciences Research Journal, 2023)
This study was designed to compare the safety and efficacy of morphine and methadone for treating NAS. A randomized, double-blind study was conducted at The Children’s Hospital & The Institute of Child Health Multan from December 2021 to December 2022. A total of 180 pregnant women were enrolled in the study, of which 114 needed treatment and were randomized (1:1) to receive morphine or methadone. Standardized Finnegan Score (FS) was used to assess infants every four hours. Methadone alternating with placebo or neonatal diluted morphine was administered to infants every four hours. The primary endpoint of the study was the duration of the hospital stay. Both the methadone and morphine groups had similar risk factors and demographic variables. There was a total of 14 adverse events equally distributed in both groups. After adjusting for the type of opioid used by the mother, it was found that the mean relative duration of hospital stay was 13% (which corresponds to the difference of 2.8 days) lower in the methadone group compared to morphine. The duration of treatment was 15% (which corresponds to a difference of 2.2 days) lower in the methadone group than in morphine. The median hospital stay with methadone was 15 days compared to 19 days with morphine (P = .005). Based on the results, it can be concluded that for the treatment of NAS, methadone had better short-term outcomes than morphine